Analysis of Web-Based Accounting Systems Based on The theory of Delone and McLean - Abdul Rahman; Rania Ekaputri (Universitas Muhammadiyah Yogyakarta, 2021)
The use of information technology in accounting is a must for companies these days. The aim of this study is to analyze the implementation of Jurnal as the online accounting system to support the financial performance of PT. Afham Karia Nusantara based on Delone and McLean approach. By using qualitative method, the study shows that the Journal as a web-based accounting application is effective in supporting the work of financial staff. This is because this application succeeds to fulfill the six dimensions of Delone and McLean's theory, namely system quality, information quality, service quality, utilization, user satisfaction, and profit. As recommendation, increasing the capability of existing features and adding features are required to improve this web-based accounting system.